The Role of Mentor Text to Increasing Students. Motivation And Engagement in Creative Writing Process - Yasmin, Feby Annisa; Fithriani , Rahmah (Institut Agama Islam Negeri Palopo, 2025)
Creative writing instruction often struggles to maintain students’ motivation and engagement. This study investigates the impact of mentor texts—exemplary literary models—on students' participation and writing proficiency in a junior high school in Medan. Using a qualitative phenomenological approach, data were collected through classroom observations, semi-structured interviews, and analysis of student writing samples involving 15 eighth-grade students over five instructional sessions. The findings reveal that mentor texts significantly enhanced students’ intrinsic motivation, increased their reading duration, and improved the application of writing techniques such as crafting engaging openings and authentic dialogue. Students also reported greater confidence in sharing their work and participating in writing discussions. However, challenges included difficulty in imitating complex writing strategies and a tendency to over-rely on mentor texts, which limited originality. The study underscores the importance of culturally relevant texts and step-by-step instructional strategies, including teacher modeling and scaffolded practice. Practical implications highlight the need for creative writing pedagogy that balances structure with autonomy. Future research should explore the long-term impact of mentor texts and their adaptability across diverse genres and educational contexts.